PENGAWASAN DAN PENGENDALIAN PT. ANGKASA PURA II DALAM PELAKSANAAN ECO-AIRPORT DI BANDARA SULTAN SYARIF KASIM II PEKANBARU - PERMATASARI, IKA; SD, ZAILI RUSLI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
PT .AngkasaPura II as the manager of the airport Sultan SyarifKasim II Pekanbaru .Implementation and development of airport construction should pay attention to eco - airport sothat the airport can function effectively and efficiently not only in the review of the technicalaspects , but also in terms of social , economic , and environmental .The concept of the theory is a theory that researchers use accordingManullangsupervision , while the indicators in this study is an oversight in the implementation ,setting standards , the division of tasks . The author combines the author of several majortheories on the concept of theory As for the factors that influence based on research found in thefield . Researchers using interviews and observation techniques using a key informant as aresource is the Engineering Dept. PT .AngkasaPura II and its employees and the communityaround the airport .The results of the study , it can be concluded that that the implementation of thesupervision and control by PT . AngkasaPura II, the concept of eco - airport airport in PekanbaruSultan SyarifKasim II as seen from a standard indicator of the determination , assessmentadministration , and also do repairs can be said has not done well . The factors that influencefactor affecting the surveillance and control activities in the implementation of eco - airport atthe airport Sultan SyarifKasim II Pekanbaru seen from all indicators ranging from HumanResources , funding / cost and participation is still not performing well , due to the lack ofsuumber adequate power , such as employee / staff of environmental monitoring and supervisionare not proportional to the number of monitoring locations . Funds needed in this implementationis not available jugak maximum of PT .AngkasaPuraII .Keywords : Monitoring , Control , Eco – Airport